Ocorrência de matrículas de ingressante autodeclarado com deficiência na Universidade Federal do Pampa - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The present study had the objective of systematizing and reflecting on data from the enrollment report of students enrolled at the Federal University of Pampa (UNIPAMPA) in under graduate and post graduate courses considering enrollment of self-declared people with disabilities (PcDs), with the perspective of subsidizing future studies and information on institutional teaching policy regarding teacher education and the challenges of teaching, taking into account the context of students with disabilities. The interest in the subject arose from my first experience as a classregent, in the curricular stage in basic education, when a student had a crisis with compatible symptomatology of Panic Disorder and I did not know how to act, recognizing my insufficient teacher training in relation to the issue. The work methodology consisted of reflections based on the compilation of data related to the student selection process, from 2006 to 2018, obtained from UNIPAMPA's Graduate Rector's Office and on electronic sites of this institution. The results show that the number of enrollments of students with disabilities in UNIPAMPA increased in the period from 2011 to 2014, reaching its peak in 2013, and soon after there was a considerable decrease in that number. It was also evidenced that the number of enrollments of self-declared enrollees PcDs in relation to the total enrollment of students entering UNIPAMPA, related to the period of the year 2006 to 2018, corresponds to 8.64% and that was not observed in the electronic institution the availability of a standard that treats and regulates an institutional policy in relation to the monitoring and the development of self-declared enrollees PcDs. Considering the above, it is possible to conclude that the national inclusive public policies gave Access to higher education, including Unipampa. However, there remain the challenges to na institutional policy that regulates teacher training, development and didactic-pedagogical accompaniment of teaching demands of the issue at hand.
Occurrence of self-declared enrollment of disabled students at the Federal University of Pampa
Keywords: Pessoas com deficiência; Acesso ao nível superior; Adversidades; People with disabilities; Access to University; Adversities; Ciências da natureza; Natural sciences; CNPQ::CIENCIAS EXATAS E DA TERRA